Critical Discourse Analysis Controversial Statement Of God Is Not An Arabic In The Perspective Of Mantiq Science - Elin Parina; Ratu Mutialela Caropeboka (IHSA Institute, 2022)
This research aims to analyze a video content of controversy the statement